Three-level neutral-point-clamped matrix converter topology - Lee, Meng Yeong (2009)
Matrix converter is a direct AC-AC converter topology that is able to directly convert energy from an AC source to an AC load without the need of a bulky and limited lifetime energy storage element. Due to the significant advantages offered by matrix converter, such as adjustable power factor, capability of regeneration and high quality sinusoidal input/output waveforms, matrix converter has been one of the AC – AC topologies that receive extensive research attention for being an alternative to replace traditional AC-DC-AC converters in the variable voltage and variable frequency AC drive applications.